MENINGKATKAN CREATIVE SELF-EFFICACY SISWA: PENGARUH MODEL CREATIVE COLLABORATIVE MATHEMATICAL REASONING PADA PEMBELAJARAN MATEMATIKA - Rizkia, Fajrul Hidayatullah; Rohati, Rohati; Kumalasari, Ade (De Fermat : Jurnal Pendidikan Matematika, 2026)
21st-century mathematics education demands students’ self-confidence in developing creative ideas; however, instructional practices remain teacher-centered, resulting in low student Creative Self-Efficacy (CSE). As a solution, a learning model that integrates creativity and collaboration through Creative Collaborative Mathematical Reasoning (CCMR) is required. This study aims to determine the effect of the CCMR model on the CSE of eighth-grade students at MTsN 1 Tanjung Jabung Barat. The research method employed was a quasi-experiment with a Non-Equivalent Control Group Design. The research population consisted of six classes, from which samples were selected using a purposive sampling technique based on an ANOVA equivalence test, resulting in class VIII A as the experimental group and class VIII B as the control group. The research instrument was a CSE questionnaire that had been tested for validity and reliability. Data analysis involved normality, homogeneity, and independent sample t-tests. The results showed a significant difference between the experimental and control classes, with a significance value of and a of The average CSE of the experimental class was higher than that of the control class. Consequently, the CCMR learning model has a positive effect on increasing students’ Creative Self-Efficacy in mathematics21st-century mathematics education demands students’ self-confidence in developing creative ideas; however, instructional practices remain teacher-centered, resulting in low student Creative Self-Efficacy (CSE). As a solution, a learning model that integrates creativity and collaboration through Creative Collaborative Mathematical Reasoning (CCMR) is required. This study aims to determine the effect of the CCMR model on the CSE of eighth-grade students at MTsN 1 Tanjung Jabung Barat. The research method employed was a quasi-experiment with a Non-Equivalent Control Group Design. The research population consisted of six classes, from which samples were selected using a purposive sampling technique based on an ANOVA equivalence test, resulting in class VIII A as the experimental group and class VIII B as the control group. The research instrument was a CSE questionnaire that had been tested for validity and reliability. Data analysis involved normality, homogeneity, and independent sample t-tests. The results showed a significant difference between the experimental and control classes, with a significance value of and a of The average CSE of the experimental class was higher than that of the control class. Consequently, the CCMR learning model has a positive effect on increasing students’ Creative Self-Efficacy in mathematics.